THE INFLUENCE OF ISLAMIC BUSINESS ETHICS AND SERVICE QUALITY ON CUSTOMER SATISFACTION OF IKHLAS BERAMAL BANGKALAN SHARIA INN - Ajeng, Ajeng Febriana Dwi Lestari; Trischa, Trischa Relanda Putra (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2024)
This research aims to determine the influence of Islamic business ethics and service quality on customer satisfaction at the Ikhlas Beramal Bangkalan Sharia Inn. The population in this study was customers who stayed at the Ikhlas Beramal Bangkalan Sharia Inn. From a population of 440 people, a sample of 100 respondents was selected which was determined using Slovin's formula. Data were retrieved using a questionnaire with a likert scale. Data analysis includes instrument tests, classical assumption tests, multiple linear regression, T tests, F tests, and determination coefficients. The results of this research test show that Islamic business ethics does not partially affect customer satisfaction, while service quality partially affects customer satisfaction. However, the results of the simultaneous F test of the two variables together influence customer satisfaction. The conclusion simultaneously, Islamic business ethics and service quality have a significant influence on customer satisfaction, while partially only service quality has an influence on customer satisfaction Sincerity Sharia Inn for Charity in Bangkalan.